Quantitative target setting in balanced scorecard method using simultaneous equations system and goal programming. Issue 9 (30th July 2019) - Farokhi, Sorour; Roghanian, Emad; Samimi, Yaser
Abstract : Purpose: The purpose of this paper is to identify the accurate cause and effect relationships among strategic objectives and also to demonstrate how decision makers can be guided in the process of defining quantitative strategic target values in the framework of balanced scorecard (BSC) and performance measurement system. Design/methodology/approach: Based on the proposed method in this research, after determining strategic objectives and developing an initial strategy map according to decision makers' opinions, simultaneous equations system (SES) was used to determine the significance of the relationships among strategic objectives in higher perspectives of the BSC and corresponding strategic objectives in lower perspectives. Afterward, desirable values for performance measures were determined based on the equations and relationships obtained through SES and were optimized by goal programming method. Findings: By applying the proposed method, a clearer picture of the associations among strategic objectives is obtained and the influence of strategic objectives on one another is determined. Afterward, optimal values for strategic objectives are determined to achieve the organization's goals. Research limitations/implications: This paper proposes a framework for constructing a strategy map and setting quantitative targets in the framework of BSC. Indeed, this paper presents a case study to demonstrate the applicability and effectiveness of the proposed approach. However, SES technique requires a greater amount of data to generate more accurate results. Although the advent of the Information Age has forced organizations' decision makers to provide sufficient information and data for business analysis, the data requirements are met. Practical implications: The presented quantitative approach is a supporting approach for improving decision makers' opinions and enabling them to reach a more accurate picture of the relationships, valuing strategic objectives and achieving strategic goals. This research also presents a case study to demonstrate the applicability of the proposed approach. The application and implication of the proposed method in banking services show that the contributions of the paper are not only theoretical, but also practical. Originality/value: The proposed method provides a novel approach for determining the most appropriate targets and applies a comprehensive and scientific model together with decision makers' opinions and experiences and has two main contributions: first, the associations among strategic objectives are investigated and obtained in an effective way by conducting the SES for the first time in the framework of BSC. Second, quantitative targets have been determined to help in achieving the long-term goals. This task has been accomplished through a combination of SES, the three-stage least squares regression analysis and optimization by using weighted goal programming method.